Ball Balancing on 3-RRS Parallel Manipulator Using PD and LQR Control - Huy-Hoang Pham; Duc-Huy Doan; Hoang-Nguyen Vo; Van-Tuong Dang; Hoang-Quoc-Bao Nguyen; Trieu-Vy Le; Thi-Thuy-Quynh Truong; Tien-Dat Tran (Robotica & Management, 2023)
Ball and plate system (BPS) is known as a nonlinear multi-input multi-output (MIMO) system that has been usually used to investigate and develop control algorithms. In this paper the study deals with a 3-RRS parallel manipulator which has a metal ball, three DC motors with linkage mechanism to a fixed base that can be a resistive touch screen . The moving base has two rotational movements, it can be rotated around the x-axis and y-axis and translated along the z-axis. The main purpose of this study is obtaining dynamics equations of motions and designing PD and LQR controllers. Through simulation and experiment, both control algorithms are proved to work well on this model.